DAMPAK PENGGUNAAN KLORIN - Achmad Hasan (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
Chlorine is a chemical substance, which has been used in many industriesfor a long time, especially in the pulp and paper industry and drinking watertreatment. Chlorine has been used in making dye, medicine, plastic, solvent and dry clean. In the sector of energy and electricity, chlorine is used in the cooling water system. Due to the lack of condition of chlorine’s storage, it will lead to the leakage of chlorine gas, which will endanger environment and health. Waste from industrial activity containing chlorine has a potential to damage environment. Chlorine also can easily react with many compounds because of its character as a strong oxidator. If chlorine and organic compounds are bound to each other, they will cause carcinogenic effect. Based on the consideration of the danger of chlorine on environment and health, many countries in the world strive to reduce its use in industries. Many alternatives and technologies have been developed to alternate the function of the chlorine.